Stature and the Standard of Living - Steckel, Richard H. (Journal of Economic Literature, 1995)
Research on the standard of living now emphasizes alternatives or supplements to the national income accounts. This paper reviews the results of two decades of research using stature as a measure of health aspects of human welfare. After comparing and contrasting stature with per capita income, I consider height patterns discovered by economic historians that challenge traditional beliefs about the past, including long-term trends, cycles in heights, and the dreadfully small stature of slave children that was followed by catch-up growth. The paper concludes with comparisons to work in development economics and suggestions for research.